Breast cancer in Jos, Nigeria: An audit on knowledge, attitude, and practices - Nanloh S Jimam; Shalkur David; Gboluwaga O Ejisun (Wolters Kluwer Medknow Publications, 2017)
Objectives: The main purpose of the study was to assess the knowledge, attitudes, and practices of women concerning breast cancer in Jos and environs. Methods: A semi-structured questionnaire was administered to 400 respondents within the age of 18 years and above residing in Jos North and South Local Government Areas of Plateau state. The data collected were then analyzed using the IBM Statistical Package for Social Sciences version 20.0 software programmer. Results: Out of the 400 study populations, only 395 (98.8%) responded to the study and 209 (53.0%) of them fall within the age 18-27 years while 89 (22.6%) were within 28 and 37 years, with only 17.8% and 6.6% in the age groups of 38-47 and ≥48 years, respectively. Two hundred and twenty (55.6%) were single, 153 (38.8%) married, while 8 (2.3%) divorced/separated, and 11 (2.8%) were widowed. The highest number (172 [43.7%]) of the respondents had secondary certificates as their highest academic qualifications, followed by diploma/The Nigeria Certificate in Education/Community Health Extension Workers (25.1%) and first degree (20.8%). Nearly 95% of the respondents have heard of breast cancer, with 30.94% of them having knowledge of the risk factors, 59.9% knew the signs and symptoms of the disease, and their main source of information (35.8%) was the media. Most of the respondents had positive attitude toward the disease, but their cancer breast screening practices were generally poor as majority of them (47.1%) had no idea of the right age to initiate self-breast examination, with majority (28.4%) confessing not practicing self-breast examination very often, neither visiting medical practitioner for breast cancer examination and care. Conclusion: The result of this study shows positive attitudes of the respondents toward the disease though high percentage of them had poor knowledge on risk factors and average knowledge of the signs and symptoms of the disease, in addition to poor breast self-examination practices.